Pengenalan Kehidupan Kampus Bagi Mahasiswa Baru (PKKMB): Bisakah membantu mahasiswa menyesuaikan diri? - Kartika, Adriana Rahmadhani; Suroso; Karolin Rista (INNER: Journal of Psychological Research, 2023)
Abstract Self-adjustment is defined as a process for the individual to make changes in the face of situations that occur in his life environment, so as to achieve good relationships with other people and the environment around the individual. One way to improve the self-adjustment of new students is with PKKMB (Introduction to Campus Life for New Students) activities, but in 2020 when the Covid-19 pandemic hit PKKMB activities were carried out online. This study aims to determine the difference in student self-adjustment in terms of students who take part in online PKKMB with students who take part in offline PKKMB. The respondents in this study were psychology students of the University of 17 August 1945 Surabaya class of 2021 who participated in the online PKKMB as many as 79 people and the class of 2022 who participated in the offline PKKMB total of 81 people. The sampling technique in this study used an accidental sampling technique. Data collection in this study used a self-adjustment scale and was analyzed using the Mann-Whitney test. The results of this study show that there is a difference in self-adjustment between students of the class of 2021 and the class of 2022 Keywords: Self-Adjustment, online PKKMB, offline PKKMB